Diet of the insectivorous bat Pipistrellus nathusii during autumn migration and summer residence. Issue 15 (28th November 2013) - Krüger, Frauke; Clare, Elizabeth L.; Symondson, William O. C.; Keišs, Oskars; Pētersons, Gunārs
Abstract Migration is widespread among vertebrates, yet bat migration has received little attention and only in the recent decades has a better understanding of it been gained. Migration can cause significant changes in behaviour and physiology, due to increasing energy demands and aerodynamic constraints. Dietary shifts, for example, have been shown to occur in birds before onset of migration. For bats, it is not known if a change in diet occurs during migration, although breeding season–related dietary preference has been documented. It is known that a diet rich in fats and the accumulation of fat deposits do increase the flight range of migratory bats. Some bat species can be regarded as long‐distance migrants, covering up to 2000 km between summer and winter roosting areas. Pipistrellus nathusii (Vespertilionidae), a European long‐distant migrant, travels each year along the Baltic Sea from north‐eastern Europe to hibernate in central and southern Europe. This study presents data on the dietary habits of migrating Pipistrellus nathusii compared with those during the breeding season. We analysed faecal samples from bats on fall migration caught at the Ornithological Field Station in Pape, Latvia and from samples collected in North‐Latvian summer roosts. We applied both morphological identification and molecular methods, as morphological methods also recognize life stages of prey and can contribute frequency data. The diets of bats on migration and breeding bats were similar, with Diptera and Lepidoptera comprising the major prey categories. However, certain prey groups could be explained by the different hunting habitats exploited during migration vs. summer residence.